2015
DOI: 10.4236/as.2015.610112
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Soil Fertility Management: Impact of <i>Mucuna</i> and <i>Tithonia</i> Biomass on Tomato (<i>Lycopersicon esculentum</i> L.) Performance in Smallholder Farming Systems

Abstract: Many views, paradigms and concepts have been advocated in recent decades on soil fertility and soil conservation across the globe in order to provide sustainable solutions to the rising food and nutrition insecurity while preserving the natural resource base. Meanwhile, food and nutrition security in Sub-Saharan Africa (SSA) is mainly achieved through smallholder farming systems that are characterized by poor and declining soil fertility, which often leads to low crop yields and low income. Hence, a field tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Refs. [34][35][36] have reported in earlier studies that such environments are ideal for termite populations to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [34][35][36] have reported in earlier studies that such environments are ideal for termite populations to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…Tithonia also increased yields of vegetables such as Celosia in Nigeria (Babajide et al, 2012), rape in Zimbabwe (Chikuvire et al, 2013) and Kales in Kenya (Mwangi and Mathenge 2014). Yields of tomatoes increased by 130% with application of tithonia compared to the control with no nutrient inputs in Cameroon (Ngosong et al, 2015). In Nigeria, the yield of okra was significantly higher in soil under tithonia fallow than under spear grass (Agbede et al, 2014).…”
Section: Response Of Crops To Tithonia Biomassmentioning
confidence: 94%
“…Despite tithonia being used on the so-called high value crops to circumvent the low returns when used on maize, very few studies have conducted economic analyses on these crops. One study with tomatoes in Cameroon (Ngosong et al, 2015) however reported very high returns (8456 USD). The BCRs for this study were however not reported hence making it difficult to determine the potential for adoption of tithonia technology for tomato production.…”
Section: Economics Of Tithonia Usementioning
confidence: 98%
“…Organic inputs and resources are able to sustain agricultural production in most areas. The use of organic inputs such as Tithonia and Mucuna mulches has been shown to be beneficial in tomato production (Ngosong et al, 2015). Some studies have advocated the use of both inorganic and organic soil amendments to increase outputs during crop production.…”
Section: Discussionmentioning
confidence: 99%
“…Integrated soil fertility management (ISFM) is especially important in production of vegetable crops which have short production cycles and require adequate supply of soil nutrients to improve crop productivity and ensure sustainable production. The ISFM is a set of agronomic practices adapted to local conditions to maximize nutrient use efficiency and sustainability (Ngosong et al, 2015). This is especially important for crops like Lycopersicon esculentum L. (tomato) with a short production cycle.…”
Section: Introductionmentioning
confidence: 99%